Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Konsumen Foto Copy Awy Comp Di Pondok Pesantren Darussalam Blokagung Tegalsari Banyuwangi - Munawir Munawir (Jurnal Istiqro, 2018)
Competition in the business world today is getting tighter. This is also felt by business people in the banking sector who are required to have better quality of service so as to satisfy the satisfaction of their customers. This study aims to analyze how much the quality of service and facilities influence customer satisfaction photo copy of awy comp at the Islamic boarding school of Darussalam Blokagung. After knowing the review of the related literature, in this study determined important variables that are strongly suspected to affect customer satisfaction, namely the quality of services and facilities. Therefore an understanding of the influence of the quality of services and facilities, with the variables that influence them can be seen as a strategic basis for the development of consumer satisfaction. So the analysis applied to this analysis to determine the effect of service quality (X1) and facilities (X2) on consumer satisfaction (Y), the analysis technique used is multiple linear regression analysis. The sample in this study were 30 consumers of copies of awy comp photos at Pondok Pesantren Darussalam Blokagung which were conducted randomly using purposive sampling technique. The results of the study indicate that there is a partial and significant influence between service quality variables on consumer satisfaction variables of 0.233 and there is a partial and significant influence between facility variables on consumer satisfaction variables of 0.819. Facility variables have a dominant influence on customer satisfaction variables rather than service quality variables. Variable quality of service and facilities simultaneously (together) and significantly affect the variables of customer satisfaction by 76.8% and the remaining 23.2% is influenced by other variables outside the research.